PENINGKATAN KAPASITAS MASYARAKAT DESA RAWAJAYA DALAM PENGELOLAAN INFRASTRUKTUR JALAN MELALUI PELATIHAN TEKNIS DAN MANAJERIAL - Sabarudin Sabarudin; Raudah Hakim; Nurul Izzah (JPMUJ, 2026)
The background of this community service initiative is rooted in the deteriorating road infrastructure conditions in Rawajaya Village, North Halmahera Regency. Significant structural damage to the village's primary pathways has created a bottleneck for local economic growth and restricted social accessibility for residents. The core problem addressed in this program is the lack of technical and managerial capacity among the local community to maintain their roads independently. This deficit has led to a chronic dependency on regional government assistance, which is often delayed or insufficient to address immediate local needs. To tackle these challenges, a comprehensive eight-week program was implemented using a multi-faceted methodology. This included participatory socialization, hands-on technical training for road repairs utilizing sustainable local materials, and intensive workshops on budget management. The novelty of this initiative lies in its integrated approach: the introduction of appropriate technology—specifically a simplified road damage measurement tool—combined with the formal establishment of a Community-Based Road Maintenance Working Group (Pokja). This structural innovation represents the first time such a localized governance model has been applied within the village. The results and discussions highlight a substantial increase in local capacity. Out of the 48 participants involved, 82% demonstrated the proficiency required to accurately diagnose various types of road distress and are now equipped to execute independent repairs. Furthermore, the community successfully drafted an accountable maintenance budget plan, marking a transition toward transparent financial self-govern ance. In conclusion, this community service demonstrates that a combination of practical, hands-on training and the formalization of working groups is highly effective in fostering rural independence regarding infrastructure management. However, the long-term sustainability of this progress remains contingent upon the commitment of the village government. Specifically, the strategic allocation of Village Funds (Dana Desa) for the collective procurement of materials and equipment is essential to ensure that the newly formed Pokja remains operational and impactful in the years to come.